Corroded RC beam repaired in flexure using NSM CFRP rod and an external steel plate. (October 2020) - Almassri, Belal; Halahla, Abdulsamee M.
Abstract: Repairing Corroded Reinforced Concrete (RC) beams has been an important area of study so far. Restoring the mechanical properties of (RC) beams which have been lost due to steel corrosion is necessary to maintain the required service life and load capacity of any (RC) structure. Despite the noticeable increase which was found during the experimental test in terms of moment capacity, stiffness and ductility of a repaired beam, the repaired corroded beam failed as a result of a premature mode of failure by the separation of concrete cover. In this paper, an analytical and Finite Element (FE) investigation are conducted on a corroded RC beam which was previously repaired with near surface mounted technique (NSM) using carbon fibre polymer rods (CFRP). A (FE) model using the commercial program ABAQUS was produced to predict the moment-deflection behavior and crack/failure pattern, it was found that using an external steel plate increases the ultimate capacity and stiffness, and it changes the mode of failure of the repaired corroded beam from a non-conventional failure mode, in which the beam cover exfoliates, to a classical and more ductile one by causing tensile reinforcement to yield, and concrete to subsequently crush in the compressed region.